Agronomic biofortification of Eruca sativa L. with iron in nutrient film technique hydroponic cultivation - Ceccherini, Guilherme José; de Lima, Bianca Machado; Lima, Tiago de Leme; Santucci, Letícia Foglia; Verruma-Bernardi, Marta Regina; Purquerio, Luis Felipe Villani; Sala, Fernando César (Australian Journal of Crop Science, 2024)
The global need for greater production of biofortified foods has increased especially in the case of hidden hunger. The agronomic biofortification of arugula with iron has become a strategy to solve the low intake of this nutrient in population. Therefore, the objective of this study was to evaluate the agronomic biofortification of two arugula cultivars in a hydroponic-NFT system, in two seasons (winter and summer), under the effect of different concentrations of iron in the nutrient solution. The experimental design was carried out in randomized blocks, in a factorial scheme with 4 concentrations of chelated iron (EDDHA) (1.8, 3.6, 5.4 and 7.2 g 1000 L-1) in the nutrient solution with fertilizers and 2 arugula cultivars (Astro and Roka), and four repetitions. The harvest was To carried out 25 days after transplanting (DAT) in winter, and in summer at 20 DAT. The agronomic analyzes were: plant diameter, number of leaves per plant, length and width of leaves, package height, fresh root mass and fresh shoot mass productivity in m², and iron content in shoots and roots. We found that the cultivation period influenced the plant's ability to accumulate iron. In summer, the faster metabolism of plants together with greater transpiration caused a faster daily saturation of Fe content by the roots. The plants showed an intense green color, with an increase in the iron concentration in the nutrient solution of both cultivars. We concluded that agronomic biofortification of arugula is possible in both cultivars. We observed that a concentration of 3.6 mg 1000L-1 of iron (iron content 9.70% above control) in winter is suitable for Astro. For cv.Roka, we indicated a concentration of 7.2 mg 1000 L-1 of iron (iron content 47.9% higher than the control), in summer. Both are recommended for consuming iron from plants for human nutrition.